Study on Model Reference Adaptive Control for Subway Pantographs - YANG Gang; SHEN Xin; KONG Guowei (Kongzhi Yu Xinxi Jishu)
The coupling performance of subway pantographs with catenaries affects the quality of current collection and the safety of trains. The rigidity of these catenaries exhibits periodicity and fluctuations due to factors such as geographical locations, seasons, and wear extents, and changes over time, making subway pantograph-catenary interactions an extremely complex system with time-varying parameters. In order to mitigate fluctuations in pantograph-catenary contact force and ensure current collection quality, this paper proposes a model reference adaptive control (MRAC) method for subway pantographs. Firstly, a catenary rigidity curve was derived for a subway line from a rigid catenary finite element model, followed by the establishment of an active control dynamics model for the subway pantograph-catenary system. Next, a reference model for the ideal active control of subway pantographs was developed under the linear quadratic optimal control (LQR) strategy. Then, the MRAC law for subway pantograph-catenary systems was formulated to enable the adaptive control of pantographs under various conditions, such as changes in catenary rigidity, degradation in pantograph performance, and variations in track and vehicle conditions. Finally, the effectiveness of the MRAC method for subway pantographs was verified through simulations. The simulation results showed that, at train speeds of 60 km/h, 70 km/h, and 80 km/h, adopting the MRAC method achieved reductions in the amplitude of pantograph-catenary contact force fluctuations by about 30% to 40%, demonstrating effective improvements in the current collection quality of subway pantographs.